Pertama Mendengar, Terakhir Dilatih: Analisis Jalur Peran Bidan dalam Kesehatan Mental Perinatal di Indonesia - Maulina, Rufidah; Khuzaiyah, Siti; Setyaningrum, Agustina Catur; Sari, Atriany Nilam; Novika, Revi Gama Hatta; Wahidah, Nurul Jannatul; Nurhidayati, Siti; Maulida, Luluk Fajria; Tursina, Elsa (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Background: Perinatal mental health disorders significantly contribute to maternal and neonatal morbidity, particularly in low- and middle-income countries (LMICs) such as Indonesia. Midwives, as frontline maternal healthcare providers, are uniquely positioned to screen for and support women experiencing mental health disorders. However, their involvement remains limited due to systemic, educational, and institutional barriers. Purpose: This study aims to understand the factors influencing midwives' knowledge and utilization of perinatal mental health screening services in Indonesia. Methods: A secondary analysis was conducted using cross-sectional data from an online survey of 300 midwives across Indonesia between June-August 2024. Variables included demographic characteristics, training experience, access to mental health resources, screening knowledge, and utilization behavior. Descriptive statistics and path analysis were used to examine direct and indirect influences on screening utilization. Results: Despite an average of 15 years of clinical experience, only 9.7% of midwives had used mental health screening tools. Just 8.7% had received formal mental health training, and only one-third had access to relevant guidelines. Screening knowledge was significantly predicted by access to structured information sources (β = 1.42; p < 0.001) and directly influenced screening utilization (β = 3.05; p < 0.001). Indirect factors, such as duration of service or interest in training, had no significant effect. Public health outreach and structured training improved access to learning materials. Conclusion: Despite strong interest among midwives, gaps in training, resources, and institutional support hinder effective mental health screening. Strengthening structured training programs and improving access to information are essential steps toward empowering midwives in perinatal mental health care. However, as most participants were from Western Indonesia, these findings should be interpreted with caution, and future studies should include broader geographic representation to better capture the national context